Characterization of Environmentally Friendly Gadolinium/Boron Flexible Thermal Neutron Absorbing Material - WANG Qi1, 2, 3, GUO Xiaolin2, 3, 4, YIN Jinnan2, 3, 5, WANG Xiaojuan2, 3, 4, YUAN Lin2, 3, 4, WANG Boyu2, 3, 4, FANG Qinglong2, 3, 4, HAN Xiaoxiang2, 3, 4, QIU Tianyi2, 3, 4, LIU Yang2, 3, 4 (Yuanzineng kexue jishu)
Generally, lead containing materials, polyethylene or epoxy resin matrix composites, stainless steel or alloy, ceramic or concrete are commonly selected for biological shielding, so as to reduce the neutron or gamma radiations below the limit level. However, these shielding materials are not able to be well attached to the peripheries of nuclear equipments or instruments with complex shapes because of their rigidity. Therefore, it is necessary to develop flexible radiation shielding materials for surface radiation hardening of some irregular structural components. Until recently, the concept of flexible radiation shielding material has aroused great interest of researchers because of their unique characteristics, and the conventional approach to prepare flexible neutron shielding composite is to add nano or micron composite containing elements with high thermal neutron absorption cross section as filler into the flexible polymer matrix. In this paper, a kind of flexible neutron absorbing material was developed by using polystyrene ethylene butadiene styrene (SEBS) as the matrix and Gd2O3 as well as B4C as functional fillers with different doping ratios through melt blending in an internal mixer. The microscopic properties of the material were characterized by SEM, EDS, XRD, and FT-IR, and the shielding performance was characterized by thermal neutron transmittance and areal uniformity tests. The results of SEM and EDS indicate that Gd2O3 and B4C micro particles are distributed uniformly in the SEBS matrix, achieving compatibility with SEBS and avoiding the problem of particle aggregation. The XRD and FT-IR results indicate that there is no chemical reaction between Gd2O3, B4C and SEBS to form chemical bond, and it belongs to a physical mixture. The thermal neutron shielding was verified through experiment and Monte Carlo simulation. The experimental transmittance of the control group material is 31.97%-35.35%, while the experimental and simulated transmittances of the experimental group material are 32.11%-36.54% and 26.26%-31.31%, respectively. Up to 6 points were uniformly selected on the surface of the (10%Gd2O3+40%B4C)/SEBS and (30%Gd2O3+40%B4C)/SEBS materials for the sake of areal transmittance uniformity test. The average thermal neutron areal transmittance of (10%Gd2O3+40%B4C)/SEBS and (30%Gd2O3+40%B4C)/SEBS are 34.34% and 31.60%, with absolute deviations of ±0.5% for all points, standard deviations of 0.33% and 0.26%, and dispersion coefficients of 0.009 6 and 0.008 2. Results indicate good uniformities of the materials, thus ensuring uniform absorption of thermal neutron. In summary, (Gd2O3+B4C)/SEBS flexible materials effectively compensate for the shortcomings of traditional rigid radiation shielding materials, and have potential application value in the field of shielding for complex and irregular structures in nuclear facilities and the wearable radiation protection clothing.